Les sanctuaires du Djebel Nefousa - Basset, René (Journal asiatique, 1899)
Text and translation of Shammākhī: Siyar, 598-600. Pp. 434-436, Arabic text. Each of the 97 translated items is enriched with many elaborate annotations and references. On pp. 427-433 Basset gives a chronological survey of governors and dynasties in Ifrīqiyā, parallel to Imams and governors of Nafūsa and Imams of Tāhert.
Keywords: Prosopographie -- Djebel Nefousa

Les sanctuaires du Djebel Nefousa - Basset, René (Journal asiatique, 1899)
Text and translation of Shammākhī: Siyar, 598-600. Pp. 434-436, Arabic text. Each of the 97 translated items is enriched with many elaborate annotations and references. On pp. 427-433 Basset gives a chronological survey of governors and dynasties in Ifrīqiyā, parallel to Imams and governors of Nafūsa and Imams of Tāhert.
Keywords: Prosopographie -- Djebel Nefousa